Testing regional convergence hypothesis using time series data: Sectoral Evidence - Hirnissa, M.T.; Dayang Affizzah, Awang Marikan; Baharom, A.H (Serials Publications, 2011)
Almost five decades, disparity in income across states in Malaysia continues to be a matter of concern. The existence of regional inequalities and the prospects that these inequalities may widen were recognized by the Malaysian government. The nine volumes of the 5-Year Malaysia Plans reflecs the sincerity of the Malaysian government in eradicating if not elevating the program of regional or states imbalances. The objective of the present study is to investigate stochastic convergence among three region (Peninsular Malaysia, Sabah and Sarawak) in Malaysia using sectoral data. Using annual data for the period 1968 to 2003 we found that Malaysian's sectoral data exhibit and week convergence between regions.